Breast Cancer Metastasis to the Axillary Lymph Nodes: Are Changes to the Lymph Node “Soil” Localized or Systemic? - Heather L Blackburn (Breast Cancer: Basic and Clinical Research, 2017)
Metastasis is a multistep process that is not well understood. Colonization of a secondary organ requires specific molecular alterations of the host microenvironment. To determine the temporal and spatial changes associated with metastatic dissemination to the axillary lymph nodes, gene expression profiles were compared between histologically normal lymph nodes from node-positive patients and tumor-free nodes from node-negative patients. Using a stringent false discovery rate correction (<0.05) for multiple hypothesis testing, we did not detect any differentially expressed genes between the lymph node groups. Thus, the presence of metastatic cells within the lymphatic system does not elicit widespread changes in gene expression through the axillary basin; rather, lymph nodes independently respond to disseminated tumor cells.